Churches Built of Stones and Words: Semiotic Analysis of the Novel “Hawksmoor” by Peter Ackroyd - Lunyova, Tetyana (Armenian Folia Anglistika, 2008)
Churches possess symbolic meaning for people and hence, are of great importance. The article presents the interpretation of the images of churches in the novel Hawksmoor by Peter Ackroyd to find out how these images are created and what they stand for. The churches in London are described in the novel as embodiment of mystic knowledge.